Disability Theology - Creamer, Deborah Beth (Religion compass, 2012)
Disability theology explores the ways in which religious traditions have engaged (or failed to engage) notions of disability and impairment, and offers constructive possibilities for inclusive theological work in the future. This essay reviews four primary models of disability (moral model, medical model, social model, and limits model) and explores how these relate to religious understandings and practices. The image of the Disabled God is highlighted, as are the ways this field has come to engage varieties of disability experience (including cognitive disabilities and autism) and diversity more broadly. Philosophical notions (such as those around normalcy or human flourishing) are explored alongside advocacy and access issues (particularly with regard to religious practices such as preaching, religious education, and biblical interpretation). Future possibilities and directions for disability theology are also proposed.